Facilitators and barriers in Academic-Practice Partnerships (APPs) between Approved Educational Institutions (AEIs) and Residential Aged Care Facilities (RACFs) during pre-registration nursing students’ placements: a systematic review protocol - Ashley Chivaura; Iseult Wilson; Deborah Rainey; Wai Yee Amy Wong (Systematic Reviews)
Abstract Background Effective Academic-Practice Partnerships (APPs) between Approved Educational Institutions (AEIs) and practice learning partners are essential for enhancing the integration of the theoretical and practical aspects of nursing education. Recent literature regarding nursing student placements in Residential Aged Care Facilities (RACFs) highlights the significance of these partnerships and a need to explore the dynamic partnerships between AEIs and RACFs to better understand their role in improving student experiences and learning outcomes. Despite the recognition of the significance of understanding these APPs, this remains a significant gap in the existing literature. Methods We will conduct a systematic review to identify facilitators and barriers to maintaining productive APPs between AEI and RACFs during pre-registration nursing student placements. Our research will involve an electronic literature search within MEDLINE, CINAHL, Web of Science, PsycINFO, and ERIC. Two independent reviewers will screen eligible papers, and a third reviewer will resolve any conflicts based on predefined inclusion and exclusion criteria. Eligible studies must have been published in English after 1990, and they should specifically address collaborative efforts between AEIs and RACFs in the context of pre-registration nursing student placements. All studies will be appraised using Caldwell’s Framework. Findings will be extracted using a standardised extraction table, and an in-depth synthesis will be conducted using thematic analysis. Discussion This systematic review addresses a gap in the literature by identifying key factors that influence APPs in the context of RACF placements. The findings from this review have the potential to guide improvements in pre-registration nursing education by informing, nurturing, and supporting collaborative relationships between AEIs and RACFs, which promote enriched experiences for nursing students during their RACF placements. The review will also provide both clinical and academic educators with a deeper understanding of what facilitates and hinders collaboration, which will empower them to facilitate effective collaboration and develop their shared capacity in supporting students. Strengthening the partnerships between AEIs and RACFs fosters a shared vision and enhances the quality of pre-registration nursing education, which improves the standard of care for RACF residents.